Linking Sustainable Business Models to Socio-Ecological Resilience Through Cross-Sector Partnerships: A Complex Adaptive Systems View. Issue 5 (May 2021) - Dentoni, Domenico; Pinkse, Jonatan; Lubberink, Rob
A flourishing literature assesses how sustainable business models create and capture value in socio-ecological systems. Nevertheless, we still know relatively little about how the organization of sustainable business models—of which cross-sector partnerships represent a core and distinctive mechanism—can support socio-ecological resilience. We address this knowledge gap by taking a complex adaptive systems (CAS) perspective. We develop a framework that identifies the key strategic, institutional, and learning elements of partnerships that sustainable business models rely on to support socio-ecological resilience. With our analytical framework, we underpin the importance of assessing sustainable business initiatives in terms of their impact on resilience at the level of socio-ecological systems, not just of organizations. Therefore, we reveal how cross-sector partnerships provide the organizational support for sustainable business models to support socio-ecological resilience. By combining the key features of CAS and the key elements of partnerships, we provide insight into the formidable task of designing cross-sector partnerships so that they support socio-ecological resilience and avoid unintended consequences.